Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acsinfecdis.2c00365
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Anti-MRSA Agents Based on Phenoxyethanol and Its Mechanism

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) poses a severe threat to public health and safety. The discovery and development of novel anti-MRSA drugs with a new mode of action are a challenge. In this study, a class of novel aryloxyethyl propiolates and their homologues as anti-MRSA agents have been designed and synthesized based on phenoxyethanol, of which compound II-39 showed high inhibitory activity against MRSA with an MIC of 0.78 μg/mL and an MBC of 3.13 μg/mL, which was better than that of vancom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…These drugs would no longer be effective once there are mutations in DNA gyrase. Herein, we selected two representative CQs to study their direct interactions with DNA using calf thymus DNA as a substrate. , Figure exposes that the characteristic UV absorption at 260 nm of DNA increased proportionally with the addition of concentration in the presence of propargyl CQ 12 and o -chlorobenzyl CQ 21g , and slight blue shifts were observed, indicating the disruption of DNA conformation after adding the active CQs. Moreover, the absorption value of the DNA-CQ 12 complex was higher than the simple sum of free DNA and propargyl CQ 12 as shown in Figure A, and the emerged hyperchromism might be due to the partial unwinding of DNA and exposure of some DNA bases caused by the noncovalent bond interaction between propargyl CQ 12 and DNA, and subsequent electronical interaction with these bases along with stronger UV absorption .…”
Section: Resultsmentioning
confidence: 99%
“…These drugs would no longer be effective once there are mutations in DNA gyrase. Herein, we selected two representative CQs to study their direct interactions with DNA using calf thymus DNA as a substrate. , Figure exposes that the characteristic UV absorption at 260 nm of DNA increased proportionally with the addition of concentration in the presence of propargyl CQ 12 and o -chlorobenzyl CQ 21g , and slight blue shifts were observed, indicating the disruption of DNA conformation after adding the active CQs. Moreover, the absorption value of the DNA-CQ 12 complex was higher than the simple sum of free DNA and propargyl CQ 12 as shown in Figure A, and the emerged hyperchromism might be due to the partial unwinding of DNA and exposure of some DNA bases caused by the noncovalent bond interaction between propargyl CQ 12 and DNA, and subsequent electronical interaction with these bases along with stronger UV absorption .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a study commissioned by the British government shows that 10 million patients will die from antimicrobial resistance annually by 2050. Moreover, a recent study revealed that about 4.95 million deaths were linked to antimicrobial resistance globally and 1.27 million deaths as a direct result of antibiotic resistance in 2019, of which methicillin-resistant Staphylococcus aureus (MRSA) directly caused approximately 100,000 deaths . Resistant bacteria such as MRSA have been recognized as the leading cause of nosocomial and community-acquired infections, which makes clinical treatment encounter tremendous challenges. , The treatment of MRSA primarily relies on vancomycin, linezolid, ceftaroline, daptomycin, tigecycline, and telavancin, of which vancomycin is one of the last resorts to address MRSA infections. , However, some clinical MRSA isolates have been shown to be resistant to almost all classes of antibiotics, including β-lactams and fluoroquinolone antibiotics. , Furthermore, it is alarming that MRSA with moderate resistance to vancomycin has emerged, which has motivated medicinal chemists to develop more novel antibacterial entities with brand-new structures and distinctive mechanisms to combat antimicrobial resistance. However, most “new” antibacterial drugs at present are still structurally limited based on traditional antibacterial molecular scaffolds, , so the cross-resistance seems to be inevitable, as it tends to be triggered between drugs with similar structural skeletons or mechanisms. , Therefore, it is urgent to exploit novel classes of antibiotics harboring different structural skeletons from that of traditional antibiotics in the case of cross-resistance. In recent years, many new compounds have been demonstrated to have good anti-MRSA activities, such as thiazole-based analogues and pyrazole-based analogues, but the effectiveness and safety of these compounds need to be further verified. Thus, more novel antibiotics with novel structural skeletons to fight MRSA infections are needed.…”
Section: Introductionmentioning
confidence: 99%
“…5,9−14 The treatment of MRSA primarily relies on vancomycin, linezolid, ceftaroline, daptomycin, tigecycline, and telavancin, of which vancomycin is one of the last resorts to address MRSA infections. 15,16 However, some clinical MRSA isolates have been shown to be resistant to almost all classes of antibiotics, including β-lactams and fluoroquinolone antibiotics. 17,18 Furthermore, it is alarming that MRSA with moderate resistance to vancomycin has emerged, 19 which has motivated medicinal chemists to develop more novel antibacterial entities with brand-new structures and distinctive mechanisms to combat antimicrobial resistance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…23 The majority of currently used antibiotics are ineffective against these group of microorganisms. 24 An additional issue arises when bacteria form biofilms that protect them from even nonresistant drugs. 25 A biofilm is an extracellular matrix (the house of the biofilm cells) made up of polysaccharides, lipids, nucleic acids, and proteins that shield them from antibiotics.…”
Section: Introductionmentioning
confidence: 99%